Data Rights Law 3.0 The Legislative Prospect. - Lian, Yuming (Peter Lang International Academic Publishers, 2021)
With a global view and a vision of our digital future, we should move forward with an understanding of data rights legislation at pace. The earlier we set the value norms around data in this digital long distance race, the more likely we will grasp the opportunities therein and embrace a future of commonly understood values. With a view to the future, the branch of Chinese law that is most likely to lead the world is that related to the digital economy. At the same time, if China wants to be amongst the world's leading digital economies, the basics to be understood and promoted most are higher quality, fairer and more sustainable institutional protection for data rights and subject-relevant interests, and the ability to offer systematic and accurate legal rules within the various digital disciplines.
Keywords: Computer science.; Law.; Sociology.; Data protection -- Law and legislation.; Data; International; Legislative; Lian; Lucy; Melville; Prospect; Rights; SSAP; Yuming